Iron protects childhood acute lymphoblastic leukemia cells from methotrexate cytotoxicity - Abedi, Marjan (Cancer Med, 2020)
Drug resistance is a fundamental clinical concern in pediatric acute lymphoblastic leukemia (pALL), and methotrexate (MTX) is an essential chemotherapy drug administered for the treatment. In the current study, the effect of iron in response to methotrexate and its underlying mechanisms were investigated in pALL cells. CCRF‐CEM and Nalm6 cell lines were selected as T and B‐ALL subtypes. Cells were pretreated with ferric ammonium citrate, exposed to the IC50 concentration of MTX and cell viability was assessed using MTT, colony formation, and flow cytometry assays. Iron‐loaded cells were strongly resistant to MTX cytotoxicity. The inhibitory effect of N‐acetyl cysteine to reverse the acquired MTX resistance was greater than that of the iron chelator, deferasirox, highlighting the importance of iron‐mediated ROS in MTX resistance. Subsequently, the upregulation of BCL2, SOD2, NRF2, and MRP1 was confirmed using quantitative RT‐PCR. Moreover, a positive correlation was demonstrated between the MRP1 expression levels and bone marrow iron storage in pALL patients. Further supporting our findings were the hematoxylin and eosin‐stained histological sections showing that iron‐treated nude mice xenografts demonstrated significantly more liver damage than those unexposed to iron. Overall, iron is introduced as a player with a novel role contributing to methotrexate resistance in pALL. Our findings suggest that the patients' bone marrow iron stores are necessary to be assessed during the chemotherapy, and transfusions should be carefully administrated.